2018
DOI: 10.1101/262303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for rapid evolution in a grassland biodiversity experiment

Abstract: Summary 23• In long-term grassland biodiversity experiments positive effects of biodiversity on 24 plant productivity commonly increase with time. Previously it was shown that 25 differential selection in monoculture and mixed-species grassland communities 26 could lead to the rapid emergence of monoculture and mixture phenotypes. 27Underlying mechanisms for such rapid phenotypic responses are however still 28 unclear. 29• We hypothesized that in biodiversity experiments pre-adapted genotypes or 30 epigenetic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…The observed shift in plant–plant interactions are consistent with several grassland studies investigating the effects of community evolution on community productivity and niche differentiation, where it was found that common rapid evolution in plant communities can lead to increases in ecosystem functioning 4,10,11,19 . We indeed observed a positive effect of common community history on the net biodiversity effect (i.e.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The observed shift in plant–plant interactions are consistent with several grassland studies investigating the effects of community evolution on community productivity and niche differentiation, where it was found that common rapid evolution in plant communities can lead to increases in ecosystem functioning 4,10,11,19 . We indeed observed a positive effect of common community history on the net biodiversity effect (i.e.…”
supporting
confidence: 89%
“…The productivity benefits of increasing species diversity rely on two main mechanisms, namely selection effects and complementarity effects, the latter encompassing both facilitation and niche differentiation 8,9 . In perennial natural grasslands, complementarity effects have been shown to increase over time due to evolutionary processes 4,10,11 . Notably, greater species complementarity can result from evolutionary changes 12 – i.e.…”
mentioning
confidence: 99%
“…Generally, however, the direction was in favour of greater leaf defence traits and reduced leaf damage in plants from monocultures in support of our hypothesis (1) suggesting greater selection for plant defence traits in monocultures compared with mixtures. While it has been hypothesized that selection of epigenetic variants may also be involved (Tilman & Snell‐Rood, ), this was previously tested for in these plant communities and epigenetic changes were found to parallel genetic changes (van Moorsel et al, ). Although differential responses between plants selected in monocultures versus mixtures to the rhizosphere microbial communities were observed, a greater performance of plants selected in monocultures versus mixtures when associated with the corresponding species’ own monoculture rhizosphere microbial community was rare, providing little support for our hypothesis (2).…”
Section: Discussionmentioning
confidence: 99%
“…c . 10 000 of 36 000 RRBS fragments in Spartina (Alvarez et al ., unpublished); >40% of bsRADseq in Heliosperma (Trucchi et al ., )) or can be annotated with known plant genes (10–15% of epiGBS loci in six grassland species; Van Moorsel et al ., ), only some of the fragments actually overlap the 5′ end of genes (Alvarez et al ., unpublished) in which increased DNA methylation has been correlated with gene silencing (Niederhuth et al ., ; Niederhuth & Schmitz, ). The functional relevance of gene body methylation outside of the 5′ end in plants appears to vary by context and across taxa (Niederhuth & Schmitz, ), and often gene body methylation is not correlated or only weakly correlated to gene expression (Bewick & Schmitz, ).…”
Section: Limitations Of Rrbs Methods For Nonmodel Speciesmentioning
confidence: 99%